Prevalensi Kolonisasi Asimptomatik Staphylococcus aureus, Pola Resistensi Antibiotik dan Perilaku Higiene Petugas Medis - Audy Tjandrawan; Lidya Handayani Tjan; Desak Nyoman Surya Suameitria Dewi; Yohanes Ary Prayoga; Natalia Yuwono; Achmad Thoriq Romadhon (Prominentia Medical Journal, 2026)
Staphylococcus aureus is an opportunistic pathogen that can colonize human skin and mucosa without causing symptoms, particularly among healthcare workers who are at risk of becoming asymptomatic carriers and contributing to nosocomial infections. This study aimed to determine the prevalence of S. aureus colonization and its antibiotic resistance patterns among healthcare workers. An observational analytic study with a cross-sectional design was conducted among healthcare workers in the ICU and Central Operating Theatre of RS Kristen Mojowarno using questionnaires and swab samples from the nasal, oropharyngeal, and axillary sites. Univariate analysis and Fisher’s Exact Test were applied for data analysis. Of 25 participants, 4 healthcare workers (16%) were colonized with S. aureus, with the nasal site being the most common (12%). Antibiotic susceptibility testing showed the highest resistance to penicillin (60%), while all isolates were 100% sensitive to erythromycin and cefoxitin. No significant association was found between handwashing frequency or nose-touching habits and S. aureus colonization (p = 1.000). This study concludes that there is no significant relationship between hand hygiene practices or nose-touching habits and S. aureus colonization among healthcare workers.